Assessment of Retinal Neurodegeneration and Choroidal Thickness in COVID-19 Patients Using Swept-Source OCT Technology - Cetinkaya, Tugba; Kurt, Muhammed M.; Akpolat, Cetin (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To analyze the central macular thickness (CMT), retinal nerve fiber layer thickness (RNFLT), ganglion cell layer thickness (GCLT), and choroidal thickness (ChT) measurements in patients with coronavirus disease 2019 (COVID-19).Methods The study was conducted cross-sectionally 4 weeks after the completed treatment of COVID-19. The diagnosis of COVID-19 was based on the polymerase chain reaction test and/or clinical and radiological findings. The patients with treated COVID-19 were enrolled in the COVID-19 group; age- and sex-matched healthy participants served as the control group. All patients in the COVID-19 group were hospitalized and treated with favipiravir, moxifloxacin, and heparin without the requirement for intubation. The measurements of CMT, RNFLT (in four quadrants), GCLT (in six sectors of two different boundaries), and ChT (in five locations) were performed by swept-source optical coherence tomography (SS-OCT).Results Similar visual acuity (p = 0.582) and intraocular pressure (p = 0.766) values were observed between the COVID-19 and control groups. Regarding SS-OCT measurements, all mean CMT, RNFLT (in four quadrants), GCLT (in six sectors of two different boundaries), and ChT (in five locations) values were similar in the COVID-19 and control groups (p > 0.05 for all). In the COVID-19 group, a statistically significant negative correlation was noted between the mean ferritin level and temporal RNFLT (r = − 0.378, p = 0.014) and a positive correlation was observed between the mean ferritin level and nasal RNFLT (r = + 0.371, p = 0.016).Conclusion SS-OCT measurements showed no retinal neurodegenerative and choroidal thickness alterations in COVID-19 patients. Nonsignificant results might be due to the examination of the patients in the early period of the COVID-19 after the treatment. Therefore, late period OCT measurements should be reviewed with new studies in the future.
Keywords: COVID-19; optical coherence tomography; retinal nerve fiber layer; ganglion cell layer; choroidal thickness